2020
DOI: 10.1128/mbio.02107-20
|View full text |Cite
|
Sign up to set email alerts
|

An Early Pandemic Analysis of SARS-CoV-2 Population Structure and Dynamics in Arizona

Abstract: In December of 2019, a novel coronavirus, SARS-CoV-2, emerged in the city of Wuhan, China, causing severe morbidity and mortality. Since then, the virus has swept across the globe, causing millions of confirmed infections and hundreds of thousands of deaths. To better understand the nature of the pandemic and the introduction and spread of the virus in Arizona, we sequenced viral genomes from clinical samples tested at the TGen North Clinical Laboratory, the Arizona Department of Health Services, and those col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…These 17 samples were from the states of Arizona, Kentucky and Massachusetts (Figure 4B). In wastewater-derived sequences from Arizona, which represents the greatest proportion of samples, the observed circulating lineages based on clinical-derived sequences are well represented (Ladner et al, 2020), with an additional nine possible circulating lineages identified.…”
Section: Resultsmentioning
confidence: 99%
“…These 17 samples were from the states of Arizona, Kentucky and Massachusetts (Figure 4B). In wastewater-derived sequences from Arizona, which represents the greatest proportion of samples, the observed circulating lineages based on clinical-derived sequences are well represented (Ladner et al, 2020), with an additional nine possible circulating lineages identified.…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 RT-PCR testing was conducted at the Sports Medicine Research and Testing Laboratory (Utah) or the Rutgers Clinical Genomic Laboratory (New Jersey). Translational Genomics Research Institute (Arizona) completed whole genome sequencing on residual diagnostic samples using standard methods ( 3 ). Sequence reads were aligned and compared with a Wuhan reference strain; all variants were identified and compared with the global GISAID SARS-CoV-2 database (>80,000 genomes).…”
Section: Investigation and Resultsmentioning
confidence: 99%
“…Only consensus genomes covering at least 90% of the reference genome with an average depth of ≥30X were used in subsequent analyses. Consensus genomes generated using these methods include those from Ladner et al 19 . Statistics reported for each sample included: total reads, number of reads aligned to reference, percent of reads aligned to reference, coverage breadth, average depth, and any SNPs and INDELs found in ≥10% of the reads at that position.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…While rapid-turnaround genomics may prove essential for outbreak containment, retrospective studies will continue to be necessary to track pathogen evolution, gauge success of public health interventions, and to evaluate pathogen/host movement and behavior. With the recent SARS-CoV-2 pandemic, retrospective studies have so-far proven successful in identifying the timing and sources of outbreaks on a local 19 and global scale 5,20 , in evaluating the effectiveness of early interventions 5 , and in identifying super-spreader events 21 . Thus, in addition to real-time monitoring, high-throughput, costeffective sequencing and analysis are needed to gain a better understanding of pandemics.…”
Section: Introductionmentioning
confidence: 99%